Religious leaders and politics: a case study of Bishop AbelTendekayi Muzorewa - Jembere, Washington (2014)
In this research project I explore whether religious leaders can be involved in Party politics and remain true to their calling, with a view of determining whether it is sustainable to argue that Bishop Muzorewa as a religious leader involved in Party politics clean in his political endeavours. The paper attempts to evaluate Bishop Muzorewa’s role in national politics and the effects his role had on the United Methodist Church. The paper will rely on data from secondary sources especially books, journals, magazines and internet materials that dwelt on Muzorewa’s activities both in the Church and Politics. In the paper, I argue that it is not sustainable to take Bishop Muzorewa as a good example of a Religious Political leader.